Life cycle assessment of inkjet printed perovskite solar cells. (1st November 2022) - Okoroafor, Tobechi; Maalouf, Amani; Oez, Senol; Babu, Vivek; Wilk, Barbara; Resalati, Shahaboddin
Abstract: Perovskite solar cells (PSCs) have moved to the forefront of emerging thin-film solar cell research in just a decade, demonstrating the most promising efficiency records. These technological advancements however, were primarily tested at laboratory scale and there remains significant issues in relation to the scalability of the deposition methods utilised. Inkjet printing, initially used for printed electronics, has recently been applied to solar cell production and demonstrated promising potential for scaling up. Despite various studies that have assessed the technical feasibility of utilising inkjet printing, their environmental performance has not been investigated. This paper, for the first time, presents a comprehensive Life Cycle Assessment (LCA) study of inkjet printing-based PSCs, on a cradle-to-gate basis using GaBi LCA software. The results were compared with those of spin-coating, as the most widely studied deposition method, and demonstrated significant improvement in all impact categories. Global warming potential (GWP) and cumulative energy demand (CED) were used as proxies to compare results obtained in this paper with available studies in the literature. The comparison demonstrated that inkjet printing of PSCs had a GWP and CED of 7.54 kg CO2 eq/m 2 and 200.18 MJ/m 2 while spin-coating had a reported median value of 74.5 kg CO2 eq/m 2 and 1204 MJ/m 2 respectively. This suggests considerable environmental advantage for the inkjet method. The paper also assesses a novel green solvent-based precursor ink investigating the environmental benefits of eliminating the toxic and hazardous solvent materials commonly used in wet chemical deposition of perovskite layers. The green solvent-based precursor ink results demonstrated significant improvement over conventional solutions with up to six orders of magnitude lower impacts. The LCA results obtained in this paper contributes to forming a full assessment of the development of scalable deposition methods such as inkjet printing by highlighting their environmental hotspots and advantages. The paper also identifies potential opportunities for perovskite precursor ink material composition improvements for sustainable development of PSCs. This will assist in addressing their associated environmental concerns in relation to the use of high impact toxic solvents. Graphical abstract: Image 1 Highlights: The environmental performance of inkjet printed PSCs was analysed for the first time. Comprehensive LCA models have been developed based on a Cradle to Gate approach. Results were compared with spin-coating and alternative green solvent precursor inks. Inkjet printing offers significant environmental benefits and scale up potentials. The novel precursor ink demonstrated up to six orders of magnitude lower impacts.